2021
DOI: 10.1021/acs.bioconjchem.1c00129
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Antibacterial Strategies of Dental Implant Materials for the Prevention of Peri-Implantitis

Abstract: As dental implants have become one of the main treatment options for patients with tooth loss, the number of patients with peri-implant diseases has increased. Similar to periodontal diseases, peri-implant diseases have been associated with dental plaque formation on implants. Unconventional approaches have been reported to remove plaque from infected implants, but none of these methods can completely and permanently solve the problem of bacterial invasion. Fortunately, the constant development of antibacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 124 publications
(196 reference statements)
0
57
0
Order By: Relevance
“…Peri-implant diseases are biological complications of dental implantation which are mainly caused by microbial bio lm [42,43]. To handle the challenge of peri-implant diseases, it is essential to improve the antimicrobial properties of dental implants [44]. Recent studies demonstrated that the antibacterial properties of the materials can be improved by the construction of nanostructured surfaces [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Peri-implant diseases are biological complications of dental implantation which are mainly caused by microbial bio lm [42,43]. To handle the challenge of peri-implant diseases, it is essential to improve the antimicrobial properties of dental implants [44]. Recent studies demonstrated that the antibacterial properties of the materials can be improved by the construction of nanostructured surfaces [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Tooth loss is another common dental disease. Nowadays, biologically inactive dental implants have become the most commonly used method for teeth restoration [ 31 ]. There is no periodontal connection built between implants and alveolar bone, leading to disability of distributing chewing pressure and failed feeling changes in temperature or pressure because of a lack of pulp tissue.…”
Section: Dpsc Sheets Applicationsmentioning
confidence: 99%
“…With the wide application of titanium implants in the restoration of missing teeth, increasing attention has been given to peri-implant inflammation. Without timely intervention, it will lead to rapid progression of inflammation, bone destruction, and ultimately failure of implant surgery [ 31 ]. One of the strategies of peri-implantitis regeneration therapy is cell sheet technology.…”
Section: Pdlsc Sheets Applicationsmentioning
confidence: 99%
“…The polymers create a hydrated layer on the surface that reduces protein adsorption. The effect varies according to the length of the polymer chains, and the uniformity and density of the polymer [ 81 ].…”
Section: Structural Enhancements and Experimental Designsmentioning
confidence: 99%